2022
DOI: 10.1093/rpd/ncac028
|View full text |Cite
|
Sign up to set email alerts
|

Does Radiological Protection Training or a Real-Time Staff Dosemeter Display Reduce Staff Doses During X-Ray-Guided Pulmonary Bronchoscopy?

Abstract: X-ray-guided interventions have increased in number and complexity. Mandatory radiological protection training includes both theoretical and practical training sessions. A recent additional training tool is real-time display dosemeters that give direct feedback to staff on their individual dose rates. Ten staff members who regularly perform pulmonary bronchoscopy wore an extra dosemeter during four 2-month periods. We controlled for the patient air kerma area product and the number of procedures in each period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
1
4
2
Order By: Relevance
“…In that setting, the staff mainly had fixed positioning during RI, which affected the possibilities to take steps away from the radiation. The occupational doses were also low [11]. In the present study, the doses to the operators (physicians) were higher than in Lundvall and Sandborg [11] due to more complex procedures and a thicker patient body part.…”
Section: Discussioncontrasting
confidence: 51%
See 4 more Smart Citations
“…In that setting, the staff mainly had fixed positioning during RI, which affected the possibilities to take steps away from the radiation. The occupational doses were also low [11]. In the present study, the doses to the operators (physicians) were higher than in Lundvall and Sandborg [11] due to more complex procedures and a thicker patient body part.…”
Section: Discussioncontrasting
confidence: 51%
“…Lasting effects of practical training and usage of a real-time display system were evaluated in a setting with experienced staff and mainly fixed positions during RI. The study reported lower median occupational doses [11]. The same method was used in the present work, but in a different clinical setting with more complex procedures and with higher patient doses.…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations